Description of a new hygrobatid genus from Chile (Acari, Hydrachnidia: Hygrobatidae) - Tuzovskij, Petr V.; Stolbov, Vitaly A. (Zootaxa, 2016)
This paper describes a new genus of the water mite family Hygrobatidae. The material was collected by V. Stolbov in 2014 and A. Prokin in 2015 in running waters in Chile. The material was sampled with a common hand net with 250 µm mesh size. The water mites were fixed in 75% ethanol.